Case report: Advances in treating ligyrophobia with third-generation ACT approach - Marino, Flavia; Doria, Germana; LoPresti, Adele; Gismondo, Stefania; Failla, Chiara; Pioggia, Giovanni (Frontiers in Psychiatry, 2024)
Background and Aims: Giulia, an 11-year-old girl diagnosed with ligyrophobia, has been experiencing intense anxiety related to loud noises since the age of two. This case report aims to explore the efficacy of Third-Wave Cognitive Behavioral Therapy, specifically Acceptance and Commitment Therapy (ACT), in addressing Giulia's anxiety and avoidance behaviors. The primary goal is to examine the impact of ACT on reducing ligyrophobic symptoms and enhancing psychological flexibility. Methods: The therapeutic intervention spanned 24 sessions and was divided into two phases. The initial phase focused on emotional competence using characters from the movie "Inside Out," aiding Giulia in recognizing and understanding her emotions. The subsequent phase targeted the six processes of psychological inflexibility identified in ACT, fostering increased flexibility. Results: Throughout the intervention, Giulia demonstrated significant improvements in anxiety symptoms, as evidenced by a decrease in Subjective Units of Distress (SUD) scores. Avoidance behaviors also diminished, and Giulia exhibited enhanced mindfulness skills. She became more cognizant of her emotional experiences and more certain of her personal ideals as a result of the therapy. Giulia's active participation and commitment to exposure exercises led to a substantial reduction in ligyrophobic reactions. Discussion: The successful application of ACT in Giulia's case suggests that targeting psychological inflexibility through mindfulness and values clarification can be effective in treating ligyrophobia in children. The integration of metaphors and creative exercises proved valuable in engaging Giulia and fostering therapeutic progress. The findings underscore the importance of a tailored, third-wave therapeutic approach in addressing specific phobias in pediatric populations.